Single domain antibody-based bispecific antibody induces potent specific anti-tumor activity. Issue 12 (1st December 2016) - Li, Jing; Zhou, Changhua; Dong, Bin; Zhong, Hong; Chen, Siqi; Li, Qing; Wang, Zhong
ABSTRACT: Bispecific antibodies have emerged as powerful therapeutic agents given their high specificity and ability to induce a potent immune response. Various bispecific antibody formats have been designed and studied regarding their applications in cancer therapy, though associated with issues of short half-life or manufacturing difficulties. Herein, a novel bispecific antibody, SS-Fc, was constructed by pairing 2 single-domain antibodies, anti-CD16 and anti-CEA, which were fused with CH3 "knobs into holes" mutations individually. SS-Fc was expressed and purified from E.coli. In vitro and in vivo experiments confirmed that SS-Fc can form a heterodimeric bispecific antibody when expressed and purified from E. coli . By engaging natural killer (NK) cells through an anti-CD16 single domain antibody, the SS-Fc bispecific antibody exhibited potent in vitro and in vivo cytotoxicity against cancer cells with carcinoembryonic antigen (CEA) expression. Thus, SS-Fc represents a novel bispecific antibody format that can be applied to a wide range of both discovery and clinical applications.